PENGARUH STRATEGI PEMASARAN ONLINE DAN PERSAINGAN TERHADAP PENINGKATAN PENJUALAN PADA RESTO ONLINE DI BANJARNEGARA - Setijadi, Setijadi; Suryani, Ratna; Maesaroh, Siti; Ariyanti, Lisa (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
ABSTRACT This study discusses the phenomenon that occurs in online restaurants in the city of Banjarnegara where online marketing strategies and competition should be a good impact on increasing sales. achieve a consistent increase in sales. The purpose of this study is to determine the effect of online marketing strategies and competition in online restaurants in Banjarnegara. This type of research is quantitative research. Data was collected by distributing questionnaires, the data obtained from the research sample were 80 people. The sampling technique of this study used the Accidental Sampling method. Multiple linear regression data analysis. Quantitative analysis in this study uses validity and reliability tests with Cronbach'a Alpha. Classical assumption test includes normality test, heteroscedasticity test and multicollinearity. The results of this study indicate that partially online marketing strategy has an effect on increasing sales, partially competition has no effect on increasing sales and simultaneously online marketing strategies and competition have an effect on increasing sales. The value of the coefficient of determination is 0.562, which means that the percentage of online marketing strategy variables and competition affects an increase in sales of 56.2% and the remaining 44.8% is influenced by other variables not included in this study.